Effects of Forced Alcohol Intake Associated with Chronic Stress on the Severity of Periodontitis: An Animal Model Study - Alessandra Nogueira Porto; Alex Semenoff Segundo; Tereza Aparecida Delle Vedove Semenoff; Fabio Miranda Pedro; Álvaro Henrique Borges; José Roberto Cortelli; Fernando de Oliveira Costa; Sheila Cavalca Cortelli (Hindawi Limited, 2012)
This study histometrically evaluated the effect of forced alcohol intake by stressed animals on the severity of ligature-induced periodontitis in rats. Thirty-two rats were randomly divided in four groups: group GAL-alcohol and ligature; group GASL-alcohol, chronic physical stress, and ligature; GNC-negative control; GPC-positive control. GAL and GASL received 20% ethanol ad libitum, and GNC received water ad libitum for 60 days. After 24 hours of exposition to alcohol intake-by GAL and GASL-immobilization was applied as a chronic stressor in the GASL group for a two-month period, six times a week, in random hours. The means of the respective groups were statistically compared (Analysis of Variance and Tukey tests, P<0.05). The most severe periodontal breakdown was observed in nonstressed animals which drank alcohol (GAL), followed by stressed animals exposed to alcohol (GASL). GASL did not differ from the positive control group (GPC). The negative control group showed the lowest values of periodontal breakdown (P<0.05). Conclusions. Non-stressed alcohol consumer animals showed the most severe pattern of periodontal breakdown. Although stressed animals which were forced to drink alcohol showed poorer periodontal status than the negative controls, their results were similar to those of positive controls.